Critical roles of PTPN family members regulated by non-coding RNAs in tumorigenesis and immunotherapy - Tang, Xiaolong; Qi, Chumei; Zhou, Honghong; Liu, Yongshuo (Frontiers in Oncology, 2022)
Since tyrosine phosphorylation is reversible and dynamic in vivo, the phosphorylation state of proteins is controlled by the opposing roles of protein tyrosine kinases (PTKs) and protein tyrosine phosphatase (PTPs), both of which perform critical roles in signal transduction. Of these, intracellular non-receptor PTPs (PTPNs), which belong to the largest class I cysteine PTP family, are essential for the regulation of a variety of biological processes, including hematopoiesis, inflammatory response, immune system, and glucose homeostasis. Additionally, a substantial amount of PTPNs have been identified to hold crucial roles in tumorigenesis, progression, metastasis, and drug resistance, and inhibitors of PTPNs have promising applications due to striking efficacy in antitumor therapy. Hence, the aim of this review is to summarize the role played by PTPNs, including PTPN1/PTP1B, PTPN2/TC-PTP, PTPN3/PTP-H1, PTPN4/PTPMEG, PTPN6/SHP-1, PTPN9/PTPMEG2, PTPN11/SHP-2, PTPN12/ PTP-PEST, PTPN13/PTPL1, PTPN14/PEZ, PTPN18/PTP-HSCF, PTPN22/LYP, and PTPN23/HD-PTP, in human cancer and immunotherapy and to comprehensively describe the molecular pathways in which they are implicated. Given the specific roles of PTPNs, identifying potential regulators of PTPNs is significant for understanding the mechanisms of antitumor therapy. Consequently, this work also provides a review on the role of non-coding RNAs (ncRNAs) in regulating PTPNs in tumorigenesis and progression, which may help us to find effective therapeutic agents for tumor therapy.